Text Informativity means Ahmed Mutter's Poetry Is A model - م.د أحمد دريس حسن (Thi Qar Arts Journal, 2021)
Abstract   This research dealt with an important vocabulary from the vocabulary of the achieved in one of the models of modern Arabic poetry represented by the poetry of a poet of the Diaspora.   The researcher took the texts (banners) of the expatriate Iraqi poet Ahmad Matar as a field of study for him, and it has been proven that the media appeared to be clear in his poetry, through its means that spread to it through poetic paradox, the conclusion of the poetic text, external intertextuality, and the omission of the intended.   The poet Ahmad Matar was able - through his suffering that he proclaimed in his poetry - to break the horizon of the recipient’s expectation, and achieve a clear textual media feature that has the characteristic of the abstaining easy, as it is an information list that raises the audience’s astonishment and curiosity. The reader's permission; It makes the recipient follow the course of the events of the poem, not refraining from it, but we find our poet intends to dispel this surprise and decode the text and the discourse closes, so that the reader does not leave the text, unless the image has become clear in his mind, and its secrets are loosened in his mind.